Quality Of Service (QoS) Analysis to Calculate Internet Network Performance Level DISKOMINFOTIK and OPD P3AP2KB Office Riau Province - Mahdhan Ragil S; Iwan Iskandar; Reski Mai Candra (Telematika, 2023)
Purpose: Among government agencies, the Office of Communication, Information and Statistics (DISKOMINFOTIK) which functions as an internet Support for Regional Apparatus Organizations (OPD), one of which is the OPD Office for Women's Empowerment, Child Protection, Population Control and Family Planning (P3AP2KB), this study was to determine the quality of the DISKOMINFOTIK network for OPD. P3AP2KB Office.Design/methodology/approach: Analyzing the quality of the internet network at DISKOMINFOTIK and in the P3AP2KB Office OPD room which has a lot of clients during busy hours, free hours, and quiet hours using the Quality Of Service (QoS) method with Throughput, packet loss, delay, TIPHON standard jitter and quantitative methodology.Findings/result: The results of the research prove that the parameter values of Throughput, packet loss, delay are at index 4 with the TIPHON measurement standard in the "Very Good" category, and jitter is index 3 with the TIPHON measurement standard in the "Good" QoS category.Originality/value/state of the art: There has been no previous research to calculate the quality of the internet network provided by DISKOMINFOTIK to Regional Apparatus Organizations (OPD), one of which is the OPD Dinas P3AP2KB, therefore this research was conducted.